Getting ready for Generation Z students - considerations on 3D printing curriculum - Popescu, Diana (2019)
As there is a worldwide adoption of 3D printing (3DP) in many activity areas, formal education becomes mandatory for acquiring theoretical knowledge and hands-on skills for an efficient use, for bringing real contributions to the development of this technology and its applications. Truly digitally natives, Gen Z students are now entering higher forms of education. They are trained by Gen X and early Gen Y professors who should be able to cope not only with students’ different set of skills and mind-set, but also, in case of 3D printing, with the media overexposure of this technology and, consequently, with a tendency of fast acquiring shallow knowledge and being auto-sufficient with this. In this context, our research examines the challenges and implications raised by 3DP curriculum aspects, providing a series of considerations and analyses based on literature review and on a long experience of teaching this topic in an engineering environment. Results of a survey aimed to understand Gen Z Romanian students’ expectations on learning and teaching 3DP are also presented. We agree the idea that teaching should be adapted to student prior knowledge, not being practical and efficient to customize it to student trait. In the same time, we consider that knowing new generation characteristics, learning habits and preferences, as a group, can definitely support teachers in choosing the right tools and methods so that to improve correct content delivery and to ensure that this content efficiently reaches audience.